Processes of change studies in late modern and present-day English - Jansen, Sandra; Siebers, Lucia (Studies in language variation ;, 2019)
"The present volume brings together leading scholars studying language change from a variety of sociolinguistic perspectives, complementing and enriching the existing literature by providing readers with a kaleidoscopic perspective of aspects of change in English from around 1700 until the present day. The volume presents a collection of in-depth studies on a broad spectrum of phonetic, lexical, grammatical and discourse variation, drawing on historical corpora, dictionaries, metalinguistic commentary, ego-documents, spoken language and survey data. Apart from advancing our knowledge of processes of language change in varieties of English, including British English, Irish English, Australian English, South African English, American English and Canadian English, the individual chapters contribute to the theoretical debates on variation and change in Late Modern as well as Present-day English"--